A STUDY OF EXPERIMENTAL FUZZY CONTROL FOR BALL AND TUBE SYSTEM - Dao, Anh-Quan; Nguyen, Ba-Thanh; Phan, Ngoc-Tho; Nguyen, Tuan-Loc; Nguyen, Tuan-Vu; Nguyen, Thanh-Cong; Le, Van-Duc-Thinh; Vo, Hoang-Trong-Thai; Le, Manh-Tin; Hoang, Ngoc-Huy; Nguyen, Hai-Dang; Le, Phuong-Tien; Le, Thi-Thanh-Hoang (Asosiasi Peneliti Sriwijaya, 2025)
This paper presents a fuzzy logic control approach for a real ball-in-tube system, which is a classical single-input, single-output (SISO) nonlinear system. The primary objective is to balance the ball's position at a fixed set point while ensuring effective tracking when the reference value changes over time. The results demonstrate the controller's ability to maintain stable ball positioning and provide smooth and responsive tracking behavior in real-time conditions.